The ethnomethodology of the bully, the bullied, and the by standers: towards reduction guidelines - Pedrigal, Joann Nnantes (Parañaque City: Olivarez College, 2013)
This ethnomethodological approach within qualitative research design sought to capture the essence of lived experience of selected bully, bullied and bystander in CAANHS-Annex. Specifically, the study focused on the following Central Question and Corollary Questions What is the nature and meaning of the experience of the bully, bullied, and the bystander in CAANHS-Annex? 1. How do selected pupils/students of CAANHS-Annex perceive and describe their experiences as a bully, bullied, and bystander? You sent 2. What are the themes and structures that emerge from these descriptions? 3. What are the forms of bullying observed in CAANHS-Annex? 4. Based on the results and findings, what bullying reduction guidelines maybe developed?
Master Thesis